SIMULATION RESULTS OF THE TIDAL CURRENT REGIME IN CAMRANII BAY USING .FINITE ELEMENT METHOD - Long, Bui Hong; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2008)
In this paper we present the experimental simulation results of the tidal currents in Cam Ranh bay, Thuy Trieu lagoon area. Finite element method was used here due to the follwing reasons: - The bottom topography of the research area is complex (bay, lagoon), and the boundary conditions are sufficient (the fluid boundary is narrow). - Measured data on the research area are comprehensive, which will enable the comparision with the calculated results. - This model has already been tested in the proposed physical environment. The simulation results of the tidal currents in Cam Ranh bay show that: - There are two typical tidal stages occuring at flood tide phase (tidal currents coming into the bay). Stage 1: The maximum tidal current directions are west-northwestward, maximum velocity of tidal currents reached 103.4 cm/s. Stage II: The peak tidal current directions are mainly north-northeastward, maximum of the peak currents at this stage was decreased by nearly 50% in comparison with stage I, reached 53.4 cm/s. -At ebb tide phase (tidal currents going out the bay), the peak tidal currents are mainly south -southwestward and their velocity may reach up to 129.6 cm/s. The comparison between calculated results and measured data of tidal currents collectedfrom 23 field stations shows that both data agree well with each other. The deviation of velocity between the measured data and maximum calculated data is 2.7 cm/s, average 0.8 cm/s, according to their absolute values. The maximum deviation of current direction is about 9.90, average is 2.60 These compared results are quite good, however they are just initial results. The model will be further developed and improved in the coming time.